Cellular Differentiation in Moss Protonemata: A Morphological and Experimental Study - Pressel, Silvia (Oxford University Press, 2008)
BACKGROUND AND AIMS: Previous studies of protonemal morphogenesis in mosses have focused on the cytoskeletal basis of tip growth and the production of asexual propagules. This study provides the first comprehensive description of the differentiation of caulonemata and rhizoids, which share the same cytology, and the roles of the cytoskeleton in organelle shaping and spatial arrangement. METHODS: Light and electron microscope observations were carried out on in vitro cultured and wild protonemata from over 200 moss species. Oryzalin and cytochalasin D were used to investigate the role of the cytoskeleton in the cytological organization of fully differentiated protonemal cells; time-lapse photography was employed to monitor organelle positions. KEY RESULTS: The onset of differentiation in initially highly vacuolate subapical cells is marked by the appearance of tubular endoplasmic reticulum (ER) profiles with crystalline inclusions, closely followed by an increase in rough endoplasmic reticulum (RER). The tonoplast disintegrates and the original vacuole is replaced by a population of vesicles and small vacuoles originating de novo from RER. The cytoplasm then becomes distributed throughout the cell lumen, an event closely followed by the appearance of endoplasmic microtubules (MTs) in association with sheets of ER, stacks of vesicles that subsequently disperse, elongate mitochondria and chloroplasts and long tubular extensions at both poles of the nucleus. The production of large vesicles by previously inactive dictysomes coincides with the deposition of additional cell wall layers. At maturity, the numbers of endoplasmic microtubules decline, dictyosomes become inactive and the ER is predominantly smooth. Fully developed cells remain largely unaffected by cytochalasin; oryzalin elicits profound cytological changes. Both inhibitors elicit the formation of giant plastids. The plastids and other organelles in fully developed cells are largely stationary. CONCLUSIONS: Differentiation of caulonemata and rhizoids involves a remarkable series of cytological changes, some of which closely recall major events in sieve element ontogeny in tracheophytes. The cytology of fully differentiated cells is remarkably similar to that of moss food-conducting cells and, in both, is dependent on an intact microtubule cytoskeleton. The disappearance of the major vacuolar apparatus is probably related to the function of caulonema and rhizoids in solute transport. Failure of fully differentiated caulonema and rhizoid cells to regenerate is attributed to a combination of endo-reduplication and irreversible tonoplast fragmentation. The formation of giant plastids, most likely by fusion, following both oryzalin and cytochalasin treatments, suggests key roles for both microtubules and microfilaments in the spatial arrangement and replication of plastids.